OPTIMIZATION OF HUMAN RESOURCE PLANNING TO SUPPORT THE FREE NUTRITIOUS MEAL PROGRAM IN ORDER TO REALIZE A RESILIENT NATIONAL DEFENSE - Mulhaq, Ilham; Kusuma, Widarta; Wijiantoro , Hendro (Journal of Industrial Engineering & Management Research, 2026)
The free nutritious meal program introduced by the Indonesian government under the Prabowo–Gibran administration represents a strategic policy aimed at improving children’s nutritional status, enhancing educational outcomes, and strengthening national resilience. This study examines the challenges and strategic role of human resource planning in supporting the implementation of the program. Using a qualitative approach, the research identifies three major issues: limited human resource competencies, inefficient logistics management, and suboptimal supervision and monitoring systems. The findings reveal that inadequate skilled personnel and weak coordination across the supply chain hinder the effectiveness of food distribution, particularly in remote areas. Furthermore, the absence of an integrated monitoring system reduces the program’s impact on improving children's nutrition. The study highlights the strategic contribution of the Indonesian Navy in addressing these challenges through comprehensive human resource planning, including capacity building, structured training, cross-sectoral logistics coordination, and technology-based monitoring systems. Strengthening these aspects is essential to ensure the sustainability and effectiveness of the program, which ultimately contributes to the development of a healthy, productive generation and supports a resilient national defense system.